Women in the Shadow of Colonialism: The Existence of Nyai in the Priangan Residency 1870-1900 - 'Aisy, Salsabila Rahadatul; Utami, Carolina Santi Muji (Universitas Islam Negeri Sumatera Utara, 2025)
This article aims to examine the dynamics of nyai life in the Priangan Residency during the Dutch colonial period between 1870 and 1900. The practice of concubinage involving native women and European men reflected gender inequality, economic pressure, and patriarchal colonial power. The term nyai is often associated with issues of morality and social stigma, but in reality they played an important role as a liaison between native and colonial society. This article also explores the legal regulations regarding mixed marriages and the fate of children from concubinage who often experienced social and legal discrimination. This phenomenon illustrates the dilemma of colonial authorities in regulating public morality amidst economic interests and power. This research uses a historical method that includes the stages of heuristics (collecting sources), source criticism (external and internal), interpretation (interpretation of historical meaning), and historiography (writing history). The sources used come from colonial archives, newspapers, Staatsblad, and documentation from institutions such as KITLV and Delpher. Through this approach, the article presents a critical analysis of the role and position of nyai in the socio-economic structure of the colonial Dutch East Indies.